18F-FDG PET and conventional imaging for assessment of Hodgkin’s disease and non Hodgkin’s lymphoma - Bucerius, J.; Herkel, C.; Joe, A. Y.; Altehoefer, C.; Finke, J.; Moser, E.; Reinhardt, M. J. (Nuklearmedizin - NuclearMedicine, 2006)
The aim of this study was to assess the diagnostic value of FDG-PET and conventional imaging (CI) in a large series of patient with Hodgkin’s disease (HD) or non-Hodgkin’s lymphoma (NHL) at three time points during their course of disease. Patients, methods: 169 consecutive lymphoma patients (69 HD; 100 NHL) were included. 193 FDG-PET studies were performed for staging at baseline in 42 cases, for post-therapeutic monitoring in 103, and for diagnosis of recurrence in 48 cases. Performance indices of sensitivity, specificity, positive (PPV) and negative predictive value (NPV), and accuracy of metabolic FDG-PET and morphological CI were calculated. Differences in staging and diagnosis of residual or recurrent lymphoma were compared. Results: FDG-PET changed staging in 36% of cases for staging at baseline, in 52% of cases for monitoring response to treatment, and in 29% for diagnosis of recurrence. FDG-PET staging results were confirmed in 80% for staging at baseline, in 74% for monitoring response to treatment, and in 50% for diagnosis of recurrence. FDGPET and CI differed significantly at monitoring response to treatment for sensitivity (0.91 versus 0.69; p<0.02), specificity (0.90 versus 0.38; p<0.00001), PPV (0.77 versus 0.42; p<0.001), and accuracy (0.83 versus 0.55; p<0.02). Conclusion: FDG-PET should be considered as the diagnostic modality of choice for post-therapeutic assessment of lymphoma patients and may be a reliable alternative to CI for staging at baseline and diagnosis of recurrence.
Keywords: Hodgkin’s disease; non-Hodgkin’s lymphoma; positron emission tomography; computed tomography; magnetic resonance imaging